2020
DOI: 10.1175/jhm-d-18-0212.1
|View full text |Cite
|
Sign up to set email alerts
|

Skill of Rain–Snow Level Forecasts for Landfalling Atmospheric Rivers: A Multimodel Assessment Using California’s Network of Vertically Profiling Radars

Abstract: The partitioning of rain and snow during atmospheric river (AR) storms is a critical factor in flood forecasting, water resources planning, and reservoir operations. Forecasts of atmospheric rain–snow levels from December 2016 to March 2017, a period of active AR landfalls, are evaluated using 19 profiling radars in California. Three forecast model products are assessed: a global forecast model downscaled to 3-km grid spacing, 4-km river forecast center operational forecasts, and 50-km global ensemble reforeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…This amplified difference owes to the differences in the watershed drainage area and in the associated reservoir flood pool storage. This outcome highlights the importance of accounting for the watershed's drainage area and reservoir capacity in estimating the watershed runoff and hence the reservoir storage responses, in addition to the precipitation total, duration, and intensity (Lamjiri et al, 2017; Ralph et al, 2019) as well as the Z FL and its forecast error (Henn et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This amplified difference owes to the differences in the watershed drainage area and in the associated reservoir flood pool storage. This outcome highlights the importance of accounting for the watershed's drainage area and reservoir capacity in estimating the watershed runoff and hence the reservoir storage responses, in addition to the precipitation total, duration, and intensity (Lamjiri et al, 2017; Ralph et al, 2019) as well as the Z FL and its forecast error (Henn et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Henn et al (2020) found average Z FL forecast errors of ~300–350 m for 30‐ to 72‐hr lead time over the Northern Sierra Nevada during 2017. Based on this finding, we apply a Z FL error of ±350 m to both watersheds and their reservoirs in our analyses (Table 1 and Figure 1a).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations